Theoretical approach to single - mod operation of bistable fabry - perot laser comtaining staturable absorber - Bao, Phung Quoc; Hoang, Dinh Van (VNU Journal of Science: Mathematics - Physics; Vol 18 No 2, 2002)
Abstract